2020
DOI: 10.1038/s41398-020-01039-2
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative and qualitative study on the neuropsychiatric sequelae of acutely ill COVID-19 inpatients in isolation facilities

Abstract: This study examined the neuropsychiatric sequelae of acutely ill patients with coronavirus disease 2019 (COVID-19) infection who received treatment in hospital isolation wards during the COVID-19 pandemic. Ten COVID-19 patients who received treatment in various hospitals in Chongqing, China; 10 age- and gender-matched psychiatric patients; and 10 healthy control participants residing in the same city were recruited. All participants completed a survey that collected information on demographic data, physical sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
150
2
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(173 citation statements)
references
References 57 publications
6
150
2
15
Order By: Relevance
“…These exceptional circumstances may disrupt the normal mourning process and expose bereaved inpatients with COVID-19 to complicated grief (Simon, 2013 ). Other factors may be involved in the occurrence of neuropsychiatric sequelae in COVID-19 patients who received treatment in the hospital isolation wards, such as the emotions experienced by patients after being infected, external factors like discrimination and quality of medical care; and psychological factors like coping and self-help behavior (Hao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These exceptional circumstances may disrupt the normal mourning process and expose bereaved inpatients with COVID-19 to complicated grief (Simon, 2013 ). Other factors may be involved in the occurrence of neuropsychiatric sequelae in COVID-19 patients who received treatment in the hospital isolation wards, such as the emotions experienced by patients after being infected, external factors like discrimination and quality of medical care; and psychological factors like coping and self-help behavior (Hao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the data in this study permitted an early outcome assessment of the clinical characteristics of gastrointestinal findings with COVID-19 in the fever clinic and can be valuable for those who need early triage through inquiry. Finally, the study did not explore psychiatric comorbidity that was reported in COVID-19 patients which is discussed by Hao et al and psychiatric comorbidity indeed could also induce multiple digestive symptoms [ 16 ]. Although gastroenterologists may pay less attention to COVID-19 symptoms of other systems (respiratory, cardiac, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In a China‐based study, Hao and colleagues 11 examined the neuropsychiatric manifestations of ten patients infected with COVID‐19 who had been treated on hospital isolation wards, comparing them with 10 age‐ and gender‐matched psychiatric patients as well as 10 healthy control participants. All participants completed a survey pertaining to their psychiatric and physical symptoms, followed by semi‐structured interviews with the COVID‐19 patients.…”
Section: The Relationship Between Covid‐19 and Mental Illnessmentioning
confidence: 99%